Makers of modern Asia - Guha, Ramachandra (Cambridge, Massachusetts : The Belknap Press of Harvard University Press, 2014)
The twenty-first century has been dubbed the Asian Century. Highlighting diverse thinker-politicians rather than billionaire businessmen, it presents eleven leaders who theorized and organized anticolonial movements, strategized and directed military campaigns, and designed and implemented political systems.
Introduction: The politics behind the Economics of Asia's rise / Ramachandra Guha -- Ch. 1. Gandhi, India and the World / Ramachandra Guha -- Ch. 2. Chiang Kai-shek and Chinese modernization / Jay Taylor. Ch. 3. Ho Chi Minh : nationalist icon / Sophie Quinn-Judge -- Ch. 4. Mao Zedong and charismatic maoism / Rana Mitter. Ch. 5. Jawaharlal Nehru: a romantic in politics / Ramachandra Guha. Ch. 6. Zhou Enlai and China's "prolonged rise" / Chen Jian -- Ch. 7. Sukarno: anticipating an Asian century / James S. Rush -- Ch. 8. Den Xioping and the China he made / Odd Arne Westad -- Ch. 9. Indira Ghandi: India and the world in transition / Srinath Raghavan -- Ch. 10. Singapore's Lee Kuan Yew : traveling light, traveling fast / Michael D. Barr -- Ch. 11. Zulkifar Ali Bhutto: in pursuit of an Asian Pakistan / Farzana Shaikh.
Includes bibliographical references and index.
Keywords: Politicians -- Asia -- Biography; Asia -- Politics and government -- 1945-; Asia -- Foreign relations -- 1945-